DESCRIPTIVE PROPAGANDIST PERIOD IS IN DEVELOPMENT OF HOUSING CO-OPERATION - Литвин, О. Ю. (Scientific Progress & Innovations, 2014)
The basic problems of development of housing co-operation, their illumination are considered in world economic literature. The analysis of researches, devoted the adopted theme is carried out. A division into the periods of publications of, is offered which outlines four periods and takes into account the specific of public policy in industry of housing co-operation. Attention is accented on that exactly housing co-operation can be one of possible mechanisms of decision of sharp housing problem in Ukraine, on the necessity of the wide informing of population about large potential of housing co-operation and use of positive oversea experience.